A meta-analysis on the immunogenicity of prototype, monovalent-adapted and bivalent vaccines against SARS-CoV-2 wildtype, Omicron BA.1 and Omicron BA.4/5 in healthy adults - Banga Ndzouboukou, Jo-Lewis; Kamara, Abdul A.; Ullah, Nadeem; Lei, Qing; Fan, Xiong-lin (Virology (New York, N.Y.), 2025)
Although COVID-19 is no longer classified as the first public health emergency, nevertheless, it still presents a serious menace to the health of the global population. Consequently, the development of COVID-19 vaccines possessing an optimal composition that can elicit broad-spectrum neutralizing responses against various SARS-CoV-2 variants is crucial. This meta-analysis aimed to compare the immunogenicity of prototype, monovalent-adapted, and bivalent COVID-19 vaccines against prototype SARS-CoV-2, Omicron BA.1 variant, and Omicron BA.4/5 subvariant in healthy adults. We utilized 4 medical databases to retrieve original studies and employed the fixed effect model to estimate pooled neutralization titers. A total of 12 studies concerning 4581 subjects were included in the meta-analysis. We found that participants who received prototype, monovalent-adapted, and bivalent vaccines as a second booster significantly developed neutralizing antibody (nAb) titers against prototype SARS-CoV-2, Omicron BA.1 variant, and Omicron BA.4/5 subvariant, with monovalent-adapted and bivalent vaccines exhibiting a higher increment. Furthermore, the bivalent(Prototype/Omicron BA.1) recombinant protein vaccine exhibited the highest increment in neutralization titers(MD = 1.95; 95 %CI:0.78–3.12; p < 0.01) against the prototype SARS-CoV-2 and Omicron BA.4/5 subvariant compared to the other vaccine regimens. Interestingly, only individuals who received the monovalent (Omicron BA.1)-adapted mRNA vaccine as a second booster showed the highest increase in neutralization titers (MD:1.37; 95 %CI:0.50–2.24; p < 0.01) against the Omicron BA.1 variant compared to the other vaccine regimens. These findings showed that bivalent recombinant protein vaccines seem more immunogenic than bivalent mRNA vaccines, and bivalent vaccines might not be superior immunogens for induced strong protective immune responses compared to monovalent-adapted vaccines. •Monovalent-adapted and bivalent vaccines showed a higher increment in neutralization titer compared to prototype vaccines.•Monovalent mRNA vaccines seem to induce a higher neutralization activity compared to bivalent vaccines.•Bivalent recombinant protein vaccine regimens seem to be more immunogenic compared to bivalent mRNA vaccines.